ON Supra α‒ Compactness In Supra topological Spaces - Ghufran A. Abbas; Taha H. Jasim (Tikrit Journal of Pure Science)
The purpose of this paper is to introduce the concept of strongly supra  continuous function, perfectly supra  continuous function and totally supra  continuous function, The relationships among these functions are studied., and investigated some properties of them. Also we introduced the concepts of supra  compact space, supra  Lindelof spaces and countably supra  compact spaces. Some basic properties are proved. At last the relationships  among supra  open, supra  continuous maps and supra  irresolute maps in supra topological spaces .